Watermelon Juice as a Non-Pharmacological Intervention for Hypertension in the Elderly: A Case Study - Supriadi, Dedi; Rahma Amelia, Rike (LPPM STIKes Muhammadiyah Ciamis, 2025)
Hypertension is a prevalent condition among older adults and is associated with serious complications, including cardiovascular disease, stroke, and renal failure. Non-pharmacological interventions, particularly the use of functional foods, have gained increasing attention due to their natural benefits and minimal adverse effects. This case study aimed to evaluate the effect of daily watermelon juice consumption on blood pressure in a 61 year old woman with a history of hypertension residing in Dusun Walahir Tonggoh, Welasari Village, Majalengka Regency. The patient received 300 mL of freshly prepared watermelon juice once daily for four consecutive days. Nursing care was delivered using the nursing process, including assessment, diagnosis, intervention, implementation, and evaluation. Blood pressure was measured before and after the intervention using a manual sphygmomanometer. The results demonstrated a clinically meaningful reduction in blood pressure, from an average of 155/90 mmHg to 140/80 mmHg, indicating the potential effectiveness of watermelon juice in lowering blood pressure. This study concludes that watermelon juice may serve as a promising, natural, and affordable complementary therapy to support hypertension management in elderly patients.